Tributários de um reservatório neotropical: habitats de desova e desenvolvimento inicial de peixes - Silva, Patricia Sarai da (2011)
The objective of this study was to analyze spatial and temporal patterns of ichthyoplankton in tributaries (Aguapeí, Verde, Pardo and Anhanduí) of Porto Primavera Reservoir, Upper Paraná River, Brazil, and its relation to some environmental variables. Specifically we sought to (I) assess whether the tributaries have similar abiotic characteristics, (II) verify that abiotic factors have more influence in the spawning of the species, (III) investigate if the species have preference for tributaries, and (IV) analyze whether the tributaries of the Porto Primavera Reservoir are really suitable environments for reproduction of fish species, especially long-distance migratory drastically affected by impoundments. Samples were taken monthly during three spawning seasons (October to March from 2007 to 2010), through horizontal hauls on the water surface at dusk, with a plankton net. The principal component analysis (PCA) was used to ascertain whether the abiotic variables differed among the tributaries. The influence of environmental variables (water temperature, pH, electrical conductivity, dissolved oxygen, turbidity, water level and discharge) in the abundance of eggs and larvae was determined using the Bioenv procedure. The Kruskal-Wallis (KW) was applied to verify spatial (tributaries: rivers Aguapeí, Verde, Pardo and Anhanduí; and habitats: main channel and lagoon) and temporal distribution patterns (month: October, November, December, January, February, and March, and spawning seasons: 1 =2007/2008, 2=2008/2009, and 3=2009/2010). The characteristic taxa of each tributary were identified through Indicator Species Analysis (IndVal). A total of 49,072 eggs, 63,857 larvae were captured. The variable that best correlated with the distribution and abundance of ichthyoplankton was the water discharge. The highest densities of eggs were noted for the Verde river, however larvae did not differ significantly among the tributaries. Eggs had the highest densities in the main channel and while larvae in lagoons. High catches of ichthyoplankton were observed from November to January, but with a peak in December. Abundance of eggs were higher in the 2009/2010 spawning season, however the larvae did not differ among spawning season. The species composition varies along the tributaries and each river has a group of indicator species. In main channel of the rivers were mainly found larvae of migratory species of short distance and long-distance and in the lagoons mainly sedentary or migratory species of short distances. The tributaries assessed are spawning grounds for many fish species and can be considered suitable for the reproduction of many long-distance migratory species. Establishment and enlargement of Conservation Units in tributaries of Porto Primavera reservoir, can help preserve habitats identified as essential spawning and nursery areas, and can be key to the maintenance and conservation of the fish species in the upper Paraná River basin.